An evaluation on the farmers' attitude on soil conservation practices (case study: agricultural area of Kardeh Dam- Iran) - Golrang, Bahram Mohammadi; Lai, Food See; Neinavaie, Shekoofeh; Mohd Noor, Khamurudin; Abd. Kudus, Kamziah; Mashayekhi, Mojgan (Marsland Press, 2013)
During the last years, natural resources in Iran have suffered severe degradations. For the sustainable and better management of these resources, various policies have been advised, the most promising of which is the management of natural resources through participation of the local people. However, it has proven difficult to involve local people in natural resources management activities. Therefore there is a great need to know the reason for the low level of participation by the local communities. This study was designed to analyze the relationship between attitude toward watershed management plans and people participation in Iran. The purpose of this study is to assess Farmers’ attitude toward the soil conservation practices in the Kushk-Abad catchment basins in the province of Khorasan Razavi. A sample of 200 farmers was randomly selected from 1200 farmers living in Kardeh catchment basin. A questionnaire was developed and revised by experts’ panel of agricultural education and promotion to confirm the validity of the questionnaire and satisfactory reliability coefficient was obtained as well. The results showed a medium level of soil conservation use by most farmers. It was also found that there is a significant positive correlation between the amount of communication channels, information resources, and access to the IT infrastructures use with our dependent variable i.e. soil conservation implementation. The hierarchical regression analysis was applied in two steps to determine the predictive variables of soil conservation practices which, at the first step, the variables pertaining to the amount of communication channels and information resources were entered followed by variables of access to the ICT infrastructures on the second step as the independent variable. They explain 16.1% of variance of soil conservation practices. The results of this research also showed that the level of the respondent’s attitude toward SCP was relatively high. This study also proved that participation in SCP is positively and significantly correlated with attitude toward SCP (r = 0.534, p =0.000).